2023
DOI: 10.1111/papt.12486
|View full text |Cite
|
Sign up to set email alerts
|

Pathways from trauma to unusual perceptual experiences: Modelling the roles of insecure attachment, negative affect, emotion regulation and dissociation

Abstract: BackgroundA range of traumas have been linked to voices (auditory verbal hallucinations) and unusual perceptual experiences (UPEs) in other perceptual‐sensory domains. Models of PTSD and positive symptoms of psychosis are insufficient in explaining the relationship between trauma and voices. The trauma‐related voices (TRV) model was developed to generate novel research in this area.AimsThis study aimed to investigate pathways from trauma to the frequency of UPEs based on a subset of hypothesised relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 119 publications
1
6
0
Order By: Relevance
“…We found that relational safety was a key element of our themes, which may support attachment‐based perspectives of trauma‐related voices (Berry et al, 2017; Berry & Bucci, 2016; Strachan, Paulik, & McEvoy, 2023) and recent evidence that insecure attachment mediates the relationship between relational trauma and hallucinatory experiences (Strachan, Paulik, Preece et al, 2023). Participants described early experiences of being alone, lonely and unprotected, and voices that unpredictably soothe or distress.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…We found that relational safety was a key element of our themes, which may support attachment‐based perspectives of trauma‐related voices (Berry et al, 2017; Berry & Bucci, 2016; Strachan, Paulik, & McEvoy, 2023) and recent evidence that insecure attachment mediates the relationship between relational trauma and hallucinatory experiences (Strachan, Paulik, Preece et al, 2023). Participants described early experiences of being alone, lonely and unprotected, and voices that unpredictably soothe or distress.…”
Section: Discussionsupporting
confidence: 72%
“…This finding is consistent with those from a randomised controlled trial ( n = 40) of ImRs for post‐traumatic nightmares that found significant reductions in perceived incompetence, which compared to other trauma‐related beliefs, was most strongly associated with PTSD symptom reduction (Long et al, 2011). Furthermore, preliminary evidence suggests that negative affect, emotion regulation deficits and dissociative coping mediate the pathway from trauma to hallucinatory experiences (Strachan, Paulik, Preece et al, 2023), and past qualitative findings suggest trauma‐focussed treatments enhance skills to constructively cope with distress (Feary et al, 2022) and stand up for oneself (Bosch & Arntz, 2021). Bandura (1997) suggests that encouragement from credible others, experiences of successful performance and physiological feedback influence self‐efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The non-clinical studies found small positive correlations between voice predisposition and both anxious and avoidant attachment (Berry et al, 2018) and a similar pattern for paranoia (Mertens et al, 2021). Strachan et al (2023) also reported a small positive association between insecure attachment and unusual perceptual experiences, while Puckett et al (2023) found no associations between voice predisposition and anxious, avoidant or disorganised attachment. When assessed through interview (rather than self-report), the association between attachment with paranoia became moderate for anxious and non-significant for avoidant attachment (Mertens et al, 2021).…”
Section: Non-clinical Studiesmentioning
confidence: 83%
“…Of these, Mertens et al (2021) and Puckett et al (2023) ran non-clinical studies and all others recruited clinical participants with diagnosed or self-reported psychosis. One study measured 'unusual perceptual experiences' in a non-clinical group (Strachan et al, 2023), and four measured 'positive symptoms' in clinical samples, but did not distinguish hallucinations, paranoia or other symptoms in the analyses (Austin, 2011;de With et al, 2023;Degnan, 2020;Pollard et al, 2020). Degnan (2020) also measured negative symptoms.…”
Section: What Is the Relationship Between Attachment Dissociation And...mentioning
confidence: 99%
See 1 more Smart Citation